Three-dimensional electron microscopy of macromolecular assemblies : visualization of biological molecules in their native state - Frank, J. (Joachim), 1940- (Oxford University Press, 2006)
Cryoelectron microscopy of biological molecules is among the hottest growth areas in biophysics & structural biology at present.